MIKRO ZONASI RESPON SPEKTRUM GEMPA DI KABUPATEN GORONTALO UTARA UNTUK KEBUTUHAN DESAIN BANGUNAN TAHAN GEMPA - Aldo, Rivaldo Inaku; Achmad, Fadly; Patuti, Indriati Martha (Composite Journal, 2022)
The issuance of SNI 1726:2019 regarding the response of the earthquake spectrum in Indonesia has not accommodated districts and sub-districts. The distribution of values on the zoning map for Indonesia is only divided by province, including Gorontalo. Gorontalo province is included in the high-risk zone because its soil motion parameter Ss is maroon with a value of 1.2–1.5g, while the ground motion S1 parameter is light brown with a constant acceleration spectrum of 60% g, Thus, it is necessary to divide the micro-scale map of the earthquake response spectrum zonation. This research aimed to analyze the value of the earthquake spectrum created with a zoning micro map in Gorontalo Utara District. This research is expected to be an initial reference in planning for the earthquake-resilient building, particularly in Gorontalo Utara District. The object of research is located in Gorontalo Utara District. This research only used secondary data obtained from several agencies, namely, BPJN Gorontalo and drilling service companies in Gorontalo Province. The secondary data used is the result of SPT (Standard Penetration Test) driling. Preparation of spectrum responses and zonation micro map referred to the guidelines of SNI 1726:2019 and the QGIS learning module. The data analyzed are based on the N-SPT data, which previously had been processed. The data obtained were processed to obtain the value that became the goal of this research by correcting the N-SPT (Standard Penetration Test) data, making the earthquake response spectrum plan, and making the response spectrum using QGIS 3.16. Gorontalo Utara District is classified as a soft-to-moderate site with an value of 9-37. The short period bedrock acceleration value SS is 1.49-2.33g. When viewed by color, Gorontalo Utara District is including in maroon to purple. The value of 1 second bedrock acceleration period S1 is 0.6-0.78. When viewed by color, it is including whitish orange to pink. The peak ground acceleration value PGA is 1.49-2.33g which, by color, is included in yellowish orange to red. The value of bedrock acceleration for a period of 1 second and the highest peak ground acceleration value occurred in Ilangata Village with SS values ​​of 2.12-2.33g, S1 0.74-0.78g and PGA values ​​0.79-0.85g. Meanwhile, the lowest value occurred in Deme 2 Village with an SS value of 1.49g, S1 0.6g and a PGA value of 0.6g. It shows that the higher the acceleration value, the greater the earthquake that occurs, and vice versa. Based on the results of this study, the acceleration value affects the estimation of the earthquake that occurs, or the acceleration is directly proportional to the force.